Avalição comparativa das intercorrências dialíticas de pacientes com lesão ranal aguda submetidos a sessões de hemodiálise prolongada de 6 e 10 horas - Albino, Bianca Ballarin [UNESP] (2013)
Extended daily dialysis (EDD) has emerged as an alternative to CRRT in the management of hemodynamically unstable AKI patients, mainly in developed countries. This trial aimed to evaluate and compare the dialytics complications occurred during different durations of EDD sessions (6 vs.10h) in critically ill AKI patients. We included patients older than 18 years with AKI associated with sepsis admitted to the intensive care unit in use of norepinephrine dose ranged from 0.3 to 0.7 ucg/kg/min. Patients were divided into two groups randomly, group 1 (G1) was performed to sessions of 6 h and group 2 (G2) of 10h. Seventy - five patients were treated with 195 sessions EDD for 18 consecutive months. Age was 61.8 ± 15.1 years, predominantly male (70.6 %), the main focus of infection was abdominal (42.6 %) and SOFA was 13.6 ± 2.7. The prevalence of hypotension, filter clotting, hypokalemia, and hypophosphatemia was 82.6, 25.3, 20 and 10.6%, respectively. The G1 was composed of 38 patients treated with 100 sessions, whereas G2 consisted of 37 patients treated with 95 sessions. The two groups were similar in male predominance (65.7 vs. 75.6%, p = 0.34), age (63.614 vs. 59.915.5, p=0.28), and SOFA (13.12.4 vs. 14.23.0, p=0.2). There was no significant difference between the two groups in the prevalence of hypotension, filter clotting (81.5 vs. 83.7%, p=0.8 e 23.6 vs. 27%, p=0.73; respectively), hypokalemia and hypophosphatemia (13.1 vs. 8.1%, p=0.71 and 18.4 vs. 21.6%, p=0.72; respectively). However, the ...